Effect of crystalline morphology on mechanical properties of PPB polymer nanofiber composite - Sangthaiyarak S. (2014)
In this work, the effects of crystalline morphology on the mechanical properties of polycaprolactone/polyvinyl alcohol/butterfly pea extract (PPB) nanofiber composite were investigated. Biopolymer nanofiber composite of PPB was fabricated by electrospinning technique using polycaprolactone concentration and distance of nozzle to ground collector of 7 wt% and 20 cm, respectively. The influence of applied voltage (vary from 15-25 kV) on the stress-strain curves was also observed. The structure and morphology of electrospun PPB nanofibers were investigated by x-ray diffraction (XRD) and scanning electron microscopy (SEM). It was found that, the degree of crystallinity increased with applied voltage and the mechanical properties was affected by the morphology of PPB nanofiber. © (2012) Trans Tech Publications.